Distinctness of strata lease scheme in Malaysia’s stratified building development: A review. - Zainal, Nur Huzaifah (Global Academic Excellence (M) Sdn. Bhd. (GAE), 2022)
Strata title is a document of ownership for a unit parcel in a stratified building such as a condominium or apartment. The idea of introducing land lease term registration onto strata title has allowed the creation of a newer type of strata scheme called the strata lease scheme. However problem arises when there is no specific law gazetted for the strata lease scheme, which has caused some confusion among scholars with different opinions on which laws apply to this concept. This is because the features of a strata lease scheme can be easily confused with a strata scheme. Therefore, this paper, referring to Malaysian laws, will review the application of the strata lease scheme concept within these legislation statues. It is found that a strata lease scheme is created under the purview of the National Land Code [Act 828]. Although, it does not have specific laws catering for the need for a strata lease scheme; instead, it is governed by several legislations to meet the requirement of its development intention. The distinctness features of a strata lease scheme can be found through specific laws which is discussed further in the paper. To conclude, Malaysian laws are sufficient to oversee the development of a strata lease scheme. However, minor amendments to the legislation may enhance the distinctness of strata lease scheme features in Malaysia.